Achatina fulica (Gastropoda: Pulmonata): Occurrence, environmental aspects and presence of nematodes in Sergipe, Brazil - G. M. Silva; M. B. Santos; C. M. Melo; V. L. S Jeraldo (Brazilian Journal of Biology, 2019)
Abstract The objective of this study was to identify the occurrence of Achatina fulica in the Great Aracaju-SE Territory. This research was developed during the months of June 2016 to May 2017. The plots methodology was used for the monthly collections, following the collection time of 20 minutes per area. The mollusks were measured and soon afterwards the parasitological analysis of the mucus and faeces was performed. Molecular identification was performed to evaluate the possible presence of Angiostrongylus sp. We observed that the occurrence of A. fulica was more representative in urban areas, especially in vacant lots with the presence of litter and decomposing materials. In the specimens of A. fulica examined were male and female nematodes of the genus Rhabditis, in the research municipalities, except in Barra dos Coqueiros. No parasites of the genus Angiostrongylus were found in the mollusks examined. The influence of the presence of litter on the plots associated with the frequency of A. fulica was statistically significant. There was a correlation between the influence of rainfall and the frequency of A. fulica. A significant relationship between moisture and frequency and nematode positivity was identified. It was also observed that the larger the mollusk, the greater the chances of being infected by nematodes. Scientific knowledge about the biology of the A. fulica species associated with human intervention such as the maintenance of land and adequate sanitary measures may be important factors for a better control of this invasive mollusk.